The Effect of Innovation and Training Capabilities on the Performance of Village Equipment in Palimanan District - Yeni, Sri; Laelatul Qodriah, Sari; Risdianto, Risdianto (Jurnal Ekuisci, 2024)
Human resources are a crucial factor in the development, progress, and change process in both organizations and government agencies. Mainly to improve human welfare productively. Palimanan District is a sub-district in Cirebon Regency. Palimanan District has 12 villages led by the village head and on the road or assisted by village officials and staff in carrying out duties and authorities. The ability to innovate is essential for the village to increase its potential in the village. The study aimed to determine the effect of innovation and training capabilities on the performance of village apparatus in the Palimanan sub-district by applying observation models, data collection, and questionnaire models in villages and Palimanan sub-districts. The research design used in this study was a descriptive analysis with a quantitative approach, aiming to determine the relationship between two or more variables. The instrument used for this study was a questionnaire sheet. This is shown from the results of the T-Test, which shows the calculated T value for the Inovas ability variable 2.431 and T table 1989, for the training variable of 5.030 and T table 1989. So it can be concluded that the calculated T value is greater than the T table where the innovation ability variable affects performance and the training variable affects performance; the F value is calculated at 35.365 > Ftable 3.11, which means there is a significant favorable influence between innovation ability and training together (simultaneously) on the performance of Palimanan sub-district village apparatus.